Multicore Software Engineering, Performance, and Tools International Conference, MSEPT 2012, Prague, Czech Republic, May 31 - June 1, 2012. Proceedings - Pankratius, Victor; Philippsen, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the International Conference on Multiscore Software Engineering, Performance, and Tools, MSEPT 2012, held in Prague in May/June 2012. The 9 revised papers, 4 of which are short papers were carefully reviewed and selected from 24 submissions. The papers address new work on optimization of multicore software, program analysis, and automatic parallelization. They also provide new perspectives on programming models as well as on applications of multicore systems.
Keywords: Computer science; Special purpose computers; Computer system failures; Computer programming; Software engineering; Programming languages (Electronic computers).; Operating systems (Computers).; Computer Science; Special Purpose and Application-Based Systems; System Performance and Evaluation; Software Engineering; Programming Languages, Compilers, Interpreters; Operating Systems; Programming Techniques; Electronic books